SHORT NOTE ON THE TAXONOMIC POSITION OF THE GENUS Nessa WALKER, 1869 WITH DESCRIPTION OF A NEW SPECIES (Orthoptera, Grylloidea, Eneopteridae) - Mello, Francisco de A. G. de (REVISTA DE AGRICULTURA, 2015)
SHORT NOTE ON THE TAXONOMIC POSITION OF THE GENUS Nessa WALKER, 1869 WITH DESCRIPTION OF A NEW SPECIES (Orthoptera, Grylloidea, Eneopteridae)